Hydrogen-assisted suspension roasting for pre-reducing lateritic nickel ore: Comparison with CO reduction - Zhe Bai; Jiahao He; Mingxing Wang; Shaokai Cheng; Shuai Yuan; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Using tea plant synomone (E, E)-α-farnesene to attract parastoid Amitus hesperidum to control Aleurocanthus spiniferus in tea plantations - Yue'er Liang; Yanjun Cheng; Manxia Wu; Shanjie Han; Baoyu Han (Crop Protection, 2026)

Suspension oxidative roasting for enhanced gold leaching from a quartz-rich refractory gold ore: Process optimization and microstructural evolution - Yan Song; Jianping Jin; Yanjun Li; Bing Zhao; Min Sun; Yuexin Han (Minerals Engineering, 2026)

Surface property evolution and floatability response of dolomite to hydrogen-based mineral phase transformation - Daolai Tian; Zhidong Tang; Peng Gao; Pengcheng Tian; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Study on the selective crushing behavior and mechanism of Dahongliutan spodumene ore under high-pressure grinding roll (HPGR) - Tianyou Yu; Yimin Zhu; Jie Liu; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Oxygen-controlled arsenic volatilization during preheating and preoxidation roasting of carbon–arsenic refractory gold ore - Hua Dong; Jianping Jin; Xinran Zhu; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

A review on the modified clay minerals for remediation of lead contaminated soil: mechanism analysis, modification methods, challenges and future prospects - Pengcheng Tian; Peng Gao; Zhidong Tang; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Efficient self-magnetization roasting of siderite via CO2 introduction - Tingbo Zhou; Yongsheng Sun; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Selective adsorption of an eco-friendly depressant poly(acrylic acid-co-maleic acid) in columbite-dolomite flotation separation - Daolai Tian; Zhidong Tang; Peng Gao; Yanjun Li; Yuexin Han (Journal of Environmental Chemical Engineering, 2026)

Mechanisms of Dissolved Organic Matter Migration in Coal Mining Subsidence Areas - Jing Xu; Liangmin Gao; Jinxiang Yang; Jieyu Xia; Han Song; Yanjun Liu; Kai Zhang; Lin Wu; Xin Shu (Mine Water and the Environment, 2026)

Sparse hierarchical recurrent modeling for real-time grade prediction in hydrogen-based hematite transformation: modeling and industrial validation - Tianyou Yu; Anh Nguyen; Yimin Zhu; Jie Liu; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Heavy metal pollution in complex polymetallic ore processing: migration mechanism, treatment technologies, and future perspectives - Pengcheng Tian; Peng Gao; Zhidong Tang; Yanjun Li; Yuexin Han (Environmental Research, 2026)

Two-step biosynthesis of benzyl alcohol from benzoyl-CoA within the phenylalanine-derived salicylic acid biosynthetic pathway in plants - Chao Zhang; Bao Zhu; Deli Sun; Xiaowen Wu; Zhihua Wu; Suna Zeng; Pingfei Han; Yaqi Wang; Hongyi Lv; Yanjun Zhang; Peng Huang; Wei Zhang; et al. (Molecular Plant, 2026)

Semi-industrial-scale detoxification of cyanide tailings by suspension oxidation roasting and feasibility evaluation for underground backfilling - Bing Zhao; Yan Song; Shuai Yuan; Peng Gao; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Kinetic mechanism and structural evolution during blank roasting of vanadium-bearing shale - Xiaolong Yu; Jianping Jin; Xinran Zhu; Zhe Bai; Shuaihou Yang; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Data-driven insights into real-world N2O emissions across conventional and hybrid vehicles: Transient impacts and driving factor identification - Huayang Zhao; Mingshen Ma; Zhou Yin; Han Jiang; Haiguang Zhao; Lei Zu; Yitu Lai; Yunjing Wang; Yanjun Wang; Hang Yin; Yan Ding (Journal of Hazardous Materials, 2026)

A review of lithium extraction from primary and secondary lithium resources using supercritical CO2 - Hongquan Wei; Jie Liu; Ruichen Wang; Yanjun Li; Yuexin Han; Chengxiu Li (Hydrometallurgy, 2026)

Structural characterization, functional properties and formation mechanism of alkali-thermal induced egg white gel: from macroscopic gel properties to molecular conformation and interactions - Shende Hu; Xiaochen Liu; Luping Gu; Cuihua Chang; Junhua Li; Xiaosan Wang; Jun Sun; Shijian Dong; Han Jiao; Yanjun Yang; Yujie Su (Food Research International, 2026)

Distinct patterns of intestinal microbiota and immune responses under acute and chronic ammonia stress in yellow catfish (Pelteobagrus fulvidraco) - Kun Xiao; Liling Nie; Shasha Zhao; Gehan Gao; Cuancheng Zhao; Yanjun Du; Rongfei Hu; Ruru Lin; Jie Wang; Man Wang; Dong Han; Lei Zhang (Aquaculture, 2026)

CircGABRB2_006 Drives Malignant Progression and EMT in Papillary Thyroid Carcinoma via the miR-296-5p/FGFR1 Axis - Chuan Wan; Yanjun Guo; Han Guo; Jingjing Zhu; Fangchao Liu; Yunyuan Zhang; Bingfei Cheng; Juanjuan Li; Ying Xin; Bingzi Dong; Weiwei Fu; Dongmei Meng; et al. (Biochemical Genetics, 2026)

Environmental and process performance implications of conversion-controlled kinetics and structure–reactivity coupling in fluidized-bed calcination of coarse limestone - Tong Chen; Xinran Zhu; Yanjun Li; Yuexin Han (Process Safety and Environmental Protection, 2026)

Hydrogen-based fluidized bed reduction of limonitic laterite nickel ore: towards co-recovery of iron and nickel and metallization enhancement - Jiaqi Wang; Yanjun Li; Jianwen Yu; Yuexin Han; Jianping Jin (Minerals Engineering, 2026)

Hydrogen fluidization roasting process to treat zinc-bearing dust: kinetics, mineral phase transformation, and magnetism - Xinran Zhu; Tong Chen; Lijie Hao; Yanjun Li; Yuexin Han (Minerals Engineering, 2026)

Enhancing nattokinase stability through synergistic interactions:Construction and mechanism analysis of multi-level encapsulation structures in fig-like gel beads - Yao Cheng; Yanjun Tong; Shanjun Tao; Shiqi Zhang; Han Jiang; Ruijin Yang (Food Research International, 2026)

Development of OSA (N, O)-acylated chitosan edible coatings loaded with cinnamon essential oil for strawberry preservation - Shiqi Zhang; Tingyi Zhou; Juncai Leng; Han Jiang; Yanjun Tong; Ruijin Yang (Food Hydrocolloids, 2026)

Hydrogen-based suspension roasting for efficient utilization of high-phosphorus oolitic hematite: Selective reduction mechanism and metallization behavior - Xuesong Sun; Yanjun Li; Zhidong Tang; Jianwen Yu; Yize Guo; Jianping Jin; Yuexin Han (Minerals Engineering, 2026)

Temperature sensitivity and rainfall heat flux drive rapid mass loss of low-latitude glaciers in the Southeastern Qinghai–Tibet Plateau - Yanjun Che; Shijin Wang; Yun Cao; Weiwei Lv; Xinggang Ma; Congzheng Han; Jian Zhong; Rong Wu (CATENA, 2026)

Simultaneous cyanide detoxification and sulfur immobilization in low-sulfur cyanide tailings via sustainable oxidation roasting: process optimization and mechanistic insights - Bing Zhao; Yan Song; Shuai Yuan; Peng Gao; Yuexin Han; Yanjun Li (Waste Management, 2026)

The role of jasmonic acid in enhancing drought resilience in mangroves: from signaling to restoration - Yi Han; Muqadas Noor; Meng Ying Huang; Wenna Wang; Muhammad Anwar; Yanjun Du (South African Journal of Botany, 2026)

Comparison of dephosphorization processes for high-phosphorus oolitic hematite based on MLA mineralogical characteristic analysis - Yusen Yu; Wenbo Li; Yongsheng Sun; Yuexin Han; Yanjun Li (Minerals Engineering, 2026)

Spatially optimized forage cultivation reconciles livestock production and wildlife conservation in Alpine grasslands - Jiawei Xu; Han Guo; Jiahao Huang; Jie Wang; Shikui Dong; Yanjun Guo (Agricultural Systems, 2026)

Prediction Method and Application of Dynamic Surface Subsidence in Deep-Buried Thick Alluvium Considering Aquifer Consolidation - Shenyi Zhang; Shanxi Wu; Han Zhang; Weijie Wei; Boyuan Cheng; Yanjun Song; Xiujuan Li; Yaochen Wang (Rock Mechanics and Rock Engineering, 2026)

Integrating very-high-resolution imagery, Sentinel-2 time-series data, and machine learning to map shrub fractional abundance across arid and semi-arid ecosystems in China - Zhonghua Liu; Yuhao Feng; Xin Cao; Josep Peñuelas; Adrià Descals; Daryl Yang; Ka Kin Cheung; Shuwen Liu; Ziyu Lin; Xiaoqiang Liu; Xiaoyong Wu; Han Ma; et al. (Remote Sensing of Environment, 2026)

Sustainable ironmaking via Hydrogen-based suspension pre-reduction of hematite: reduction mechanisms, bonding behavior, and comparison with carbon routes - Xuesong Sun; Yanjun Li; Jianwen Yu; Yize Guo; Yuexin Han (Minerals Engineering, 2026)

Increasing carbon mitigation through enhanced oil recovery - YanJun Lu; QianBo Fan; JinXuan Han; ManPing Yang; JianGuo Ma; DaXin Zhou; HongJian Zhu; Yu Qi; HaoRan Ge (International Journal of Greenhouse Gas Control, 2026)

A new method for efficient recovery of boron from boron-bearing iron concentrate: low-temperature fluidized selective reduction and magnetic separation - Jianwen Yu; Xuanxiong Kang; Peiyu Li; Xuesong Sun; Yanjun Li; Yuexin Han; Zhongxu Qi; Dayon Sun (Minerals Engineering, 2026)

Comprehensive utilization of Bayan Obo polymetallic ore: A review - Qiang Zhang; Yongsheng Sun; Yuexin Han; Yanjun Li; Peng Gao (Minerals Engineering, 2026)

Multidimensional comparative study on the efficacy and mechanisms of radiofrequency and thermal induction inactivation of Aspergillus Niger spore - Yudi Liu; Yanjun Tong; Han Huang; Wei Zhao; Ruijin Yang (Innovative Food Science & Emerging Technologies, 2026)

N2O and NO formation influenced by metal elements during coal pyrolysis and char combustion - Yanjun Zuo; Zhaoxin Wan; Haiyang Li; Ping Liu; Xiaoshuo Liu; Yingchuan Zhou; Zhi Han; Yufeng Duan (Fuel, 2026)

Influence and optimization of hydrogen-based mineral phase transformation on grinding characteristics of polymetallic oxide and recovery of valuable elements by response surface methodology - Pengcheng Tian; Peng Gao; Zhidong Tang; Yanjun Li; Yuexin Han (Minerals Engineering, 2025)

Thermal decomposition behavior of boron-bearing iron concentrate under nitrogen atmosphere: Kinetics, mineral phase transformation and microstructure evolution - Jianwen Yu; Xuanxiong Kang; Peiyu Li; Xuesong Sun; Yanjun Li; Yuexin Han; Zhongxu Qi; Dayon Sun (Minerals Engineering, 2025)

Carbon footprint assessment and emission reduction analysis of wood flooring based on life-cycle assessment: six cases from China - Jia Guo; Haigang Wang; Luqing Gao; Han Zhu; Daxin Liang; Zefang Xiao; Yonggui Wang; Wenyan Jing; Jianping Pan; Yanjun Xie (Clean Technologies and Environmental Policy, 2025)

Assessment of habitat characteristics in typical seagrass bed ecosystems along the coast of Changhai County, Dalian - Yuchen Chu; Jun Yang; Juncheng Yin; Jie Tian; Jun Song; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; Yanjun Wang; Qian Sun; Quanxiang Meng; et al. (Acta Oceanologica Sinica, 2025)

From iron concentrate to clean steel: A green short-process production technology centered on preparing high-purity iron concentrate - Wencheng Ge; Jie Liu; Tianjiao Chang; Yanjun Li; Yongsheng Sun; Shumin Zhang; Yuexin Han; Yimin Zhu (Minerals Engineering, 2025)

Light-driven release of 6PPD and formation of 6PPD-Q from tire and road wear particles: Mechanisms and cytotoxicity - Danfeng Zhang; Bo Yin; Wen Zhang; Shiyu Wei; Puxing Zhang; Tianyuan Su; Yanjun Liu; Xiwang Tang; Han Wang; Chengfang Yang; Zhuozhi Ouyang; Guining Lu; et al. (Journal of Hazardous Materials, 2025)

N2O and NO formation and inhibition influenced by calcium (Ca) during coal char combustion - Zhi Han; Ping Liu; Yanjun Zuo; Yingchuan Zhou; Xiaoshuo Liu; Xunlei Ding; Jianming Xue; Yufeng Duan (Fuel, 2025)

Mechanisms driving spectral properties and their associations with above-ground biomass dynamics in a temperate forest - Pengcheng Jiang; Han He; Zikun Mao; Yanjun Su; Mengxu Zhang; Zhichao Xu; Meihui Zhu; Jin Yin; Hongyi Jiang; Shuai Fang; Xugao Wang (Forest Ecology and Management, 2025)

Global sustainable pathway for lithium metal production: A critical review and best practice guide - Ruichen Wang; Yuexin Han; Yanjun Li; Feilong Zhang; Chunge Dang; Zhiguo Yuan; Jie Liu (Chemical Engineering Journal, 2025)

Genome and transcriptome analysis provide insights into the genetics and breeding of Salix suchowensis growth traits - Wei Liu; Shaobo Gu; Mingjia Zhu; Yu Han; Xiaogang Dai; Huaitong Wu; Tongming Yin; Linjie Guo; Landi Feng; Yanjun Zan; Jianquan Liu (New Forests, 2025)

Synergistic defense mechanisms between soybean disease resistance genes and stomatal regulation - Jikai Li; Yanjun Li; Chunmei Luo; Shubo Zhou; Jemaa Essemine; Weibo Han; Mingnan Qu (Euphytica, 2025)

Reliable enrichment monitoring and removal of CrO42− and S2− using multivalent W-doped Ag quantum-dot biomimetic nanozyme - Ruhui Shang; Yanjun Han; Huitian Zhi; Xujie Wang; Yingchao Yang; Xiao Zhu; Lei Hu; Zhengquan Yan (Analytica Chimica Acta, 2025)

Enhanced hydrogen-based reduction of hematite by bastnaesite: Kinetics and microstructural evolution mechanisms - Lingbo Zhao; Peng Gao; Bing Zhao; Zhenyue Zhang; Xiangyan Kong; Yuexin Han; Yanjun Li (Minerals Engineering, 2025)

Strategy to kill two birds with one stone: Contribution of hydrogen-based mineral phase transformation on enhancing the grinding and flotation characteristics of bastnaesite and fluorite - Pengcheng Tian; Jian Zhang; Peng Gao; Zhidong Tang; Yanjun Li; Yuexin Han (Process Safety and Environmental Protection, 2025)

Electric field distribution and selective liberation in magnetite quartzite under high voltage pulse discharge - Yonghong Qin; Ziyu Yang; Yuexin Han; Peng Gao; Yanjun Li; Ningyu Zhang (Minerals Engineering, 2025)

Enhanced pre-selection of spodumene via ultraviolet-induced fluorescence and improved YOLOv8 deep learning algorithm - Tianyou Yu; Yimin Zhu; Jie Liu; Yuexin Han; Yanjun Li (Minerals Engineering, 2025)

The effect and mechanism analysis of calcium and magnesium between the blank roasting-leaching process of vanadium shale - Jianping Jin; Xiaolong Yu; Zhe Bai; Zhenya Zhou; Yuexin Han; Yanjun Li (Fuel, 2025)

Risk factors for severe lower respiratory tract infection among children under 5 years of age hospitalized with respiratory syncytial virus - Yanjun Wang; Yuanxuan Xiang; Ruohong Jin; Bin Li; Xingxing Feng; Qian Han; Xishu Deng; Yunfang Lu; Chengyan Zhang; Shufang Xiao (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Optimization of discharge parameters for high-voltage pulse crushing technology − A review - Bo Zhang; Rui Han; Peng Gao; Shuai Yuan; Yanjun Li; Honghao Zhang (Minerals Engineering, 2025)

Desulfurization, desilication, and the separation and recovery of iron from bauxite: A review - Qinglong Fan; Shuai Yuan; Rui Han; Yanjun Li; Jiahao He; Xiaobin Ning (Minerals Engineering, 2025)

Divergent Flowering Time Responses to Increasing Temperatures Are Associated With Transcriptome Plasticity and Epigenetic Modification Differences at FLC Promoter Region of Arabidopsis thaliana - Yu Han; Li Liu; Mengyu Lei; Wei Liu; Huan Si; Yan Ji; Qiao Du; Mingjia Zhu; Wenjia Zhang; Yifei Dai; Jianquan Liu; Yanjun Zan (Molecular Ecology, 2025)
Understanding the genetic, and transcriptomic changes that drive the phenotypic plasticity of fitness traits is a central question in evolutionary biology. In this study, we utilised 152 natural Swedish Arabidopsis thaliana accessions with re‐sequenced genomes, transcriptomes and methylomes and measured flowering times (FTs) under two temperature conditions (10°C and 16°C) to address this question. We revealed that the northern accessions exhibited advanced flowering in response to decreased temperature, whereas the southern accessions delayed their flowering, indicating a divergent flowering response. This contrast in flowering responses was associated with the isothermality of their native ranges, which potentially enables the northern accessions to complete their life cycle more rapidly in years with shorter growth seasons. At the transcriptome level, we observed extensive rewiring of gene co‐expression networks, with the expression of 25 core genes being associated with the mean FT and its plastic variation. Notably, variations in FLC expression sensitivity between northern and southern accessions were found to be associated with the divergence FT response. Further analysis suggests that FLC expression sensitivity is associated with differences in CG, CHG and CHH methylation at the promoter region. Overall, our study revealed the association between transcriptome plasticity and flowering time plasticity among different accessions, providing evidence for its relevance in ecological adaptation. These findings offer deeper insights into the genetics of rapid responses to environmental changes and ecological adaptation.

Hydrogen-based fluidization direct reduction of high purity iron concentrate: Experimental optimization and mechanism analysis - Tingbo Zhou; Yongsheng Sun; Yuexin Han; Yanjun Li (Minerals Engineering, 2025)

Preparation, characterization and antimicrobial properties of double lysine-modified chitosan and its preservation ability in chicken meat refrigeration - Bin Dong; Yijie Wang; Lili Han; Guirong Cui; Yanjun Lin; Zhiwei Su; Guozhong Zhao (Food Chemistry, 2025)

Multi-scale coupling measurement and driving factor analysis between carbon emission from energy consumption and ecological environment—The case study of Pearl River Delta urban agglomeration - Yanjun Wang; Mengru Song; Yongshun Han; Yichang Wang (Sustainable Cities and Society, 2025)

Organic substitution enhances soil quality, soil microbial community stability, foxtail millet productivity, and grain quality in North China - Mengen Nie; Xue Gao; Lijie Zhao; Genlan Han; Yanyan Duan; Ruihua Han; Shuqi Dong; Yongling Li; Huiling Du; Xiangyang Yuan; Yanjun Yang (Journal of Environmental Management, 2025)

Single-B-cell cloning and recombinant antibodies generation to analyze the antigenicity of porcine reproductive and respiratory syndrome virus nonstructural protein 12 - Hongyong Duan; Chaozhi Tang; Song Han; Nan Yang; Shumao Wang; Fei Gao; Yanjun Zhou; Guangzhi Tong; Kuan Zhao; Liwei Li (Veterinary Microbiology, 2025)

Dual-template molecularly imprinted magnetic covalent organic framework for selective extraction of bisphenols - Shu-hui Huo; Mengya Qin; Xiaonan Zhang; Pengxin Zhou; Junhao Liu; Xiaoqiang Yao; Zhengang Han; Zhentong Zhu; Yanjun Feng; Zhilan Wang; Xiaoquan Lu (Chemical Engineering Journal, 2025)

De novo design of dual-detection fluorescent sensors for bisulfite and copper (II) ion based on cascade activation - Tian Tan; Wenyu Xi; Chenxu Duan; Ying Han; Peikun Xiao; Hongqi Yin; Hong Huang; Xulang Chen; Yanjun Hu; Xiaohuan Huang (Analytica Chimica Acta, 2025)

Design and properties of graphene film/polymer square-wave-like composites - Yanjun Xu; Shasha Wang; Xianxian Sun; Wenbo Han; Yibin Li (Chemical Engineering Journal, 2025)

Pilot-scale recovery of iron from refractory specularite ore using hydrogen-based mineral phase transformation technology: Process optimization, mineral characterization, and green production - Pengcheng Tian; Peng Gao; Mingxing Wang; Yanjun Li; Yuexin Han (Journal of Cleaner Production, 2025)

Effects of fine particulate matter bound heavy metals on intentional self-harm deaths in Guangzhou, China, insight from core chemical constituents - Chunyan Gui; Han Zhang; Zhanlu Lv; Tao Liu; Shengbing Yu; Yanjun Xu; Hualiang Lin; Jianpeng Xiao; Wenjun Ma; Bin Luo; Ling-Chuan Guo (International Journal of Biometeorology, 2025)

Numerical study of regular wave dynamics for optimizing coral reef restoration - Jiuming Han; Yanjun Li; Xizeng Zhao; Tao Liu; Yanzhen Gu; Shuangyan He; Peiliang Li; Ruili Sun (Ocean Engineering, 2025)

Iron-doped titanium lithium-ion Sieves@Sodium alginate-enhanced carboxymethyl cellulose aerogels: A synergistic leap in adsorption and sustainability - Shengkai Liu; Birong Yan; Yu Han; Wei Wang; Yimin Shi; Yonggui Wang; Huiling Li; Junhao Liu; Zefang Xiao; Daxin Liang; Yanjun Xie (Journal of Cleaner Production, 2025)

A new analysis of an application of low-carbon pre-selecting technology (LCPT) for minerals: An evolutionary game model among stakeholders - Tianyou Yu; Yimin Zhu; Jie Liu; Yuexin Han; Yanjun Li (Journal of Cleaner Production, 2025)

Recent advances in biosynthesis mechanisms and yield enhancement strategies of erythritol - Wenli Yang; Xiangying Zhao; Mo Han; Yuchen Li; Yanjun Tian; Zhangbo Rong; Jiaxiang Zhang (Critical Reviews in Food Science and Nutrition, 2024)

Multi-scale structural and In vitro digestion properties of amino acids-tiger nut starch complexes and applications in noodles - Shiqi Zhang; Yiming Jiang; Zihan Gao; Juncai Leng; Tingyi Zhou; Han Liu; Chenlu Zhu; Yanjun Tong; Wenbin Zhang; Ruijin Yang (Food Bioscience, 2024)

High-pressure processing for pickled crabs: Safety, quality and flavor assessment and correlation analysis of spoilage indicators - Han Huang; Yudi Liu; Yanjun Tong; Wei Zhao; Xiaomei Lyu; Ruijin Yang (Food Bioscience, 2024)

Assessing the spatial-temporal impacts of underlying surfaces on 3D thermal environment: A field study based on UAV vertical measurements - Fengtao Qian; Yanjun Hu; Renwu Wu; Hai Yan; Dingsheng Wang; Zhoubing Xiang; Kechun Zhao; Qian Han; Feng Shao; Zhiyi Bao (Building and Environment, 2024)

Critical analysis of using recycled wax oils in asphalt binder considering exudation effects - Han Liu; Bo Su; Haibo Ding; Yanjun Qiu (Fuel, 2024)

A novel selective collector MIBATC and its performance on flotation separation of chalcopyrite from sphalerite and pyrite - Xuesong Sun; Jianwen Yu; Yanjun Li; Yuexin Han; Peng Gao (Minerals Engineering, 2024)

Bamboo-inspired lightweight, mechanically-stable and vibration-damping structural members for engineering applications - Shanyu Han; Deyue Li; Fuming Chen; Mingqian Wang; Yubing Leng; Yanjun Li; Hanzhou Ye; Ge Wang (Engineering Structures, 2024)

New insights of selective rupture of synthetic sample under high voltage pulse discharge: A numerical simulation of electric field distribution - Yonghong Qin; Ziyu Yang; Yuexin Han; Peng Gao; Yanjun Li; Ningyu Zhang; Jianming Gao (Minerals Engineering, 2024)

Which street is hotter? Street morphology may hold clues -thermal environment mapping based on street view imagery - Yanjun Hu; Fengtao Qian; Hai Yan; Ariane Middel; Renwu Wu; Minghui Zhu; Qian Han; Kechun Zhao; Han Wang; Feng Shao; Zhiyi Bao (Building and Environment, 2024)

New approach to reduce carbon emissions by hydrogen reduction of boron-bearing iron concentrate in a fluidized bed: Reduction kinetics and microstructure analysis - Peiyu Li; Jianwen Yu; Yanjun Li; Peng Gao; Yuexin Han (Minerals Engineering, 2024)

Attribution of streamflow changes during 1961–2019 in the Upper Yangtze and the Upper Yellow River basins - Shanshan Wen; Buda Su; Jinlong Huang; Yanjun Wang; Simon Treu; Fushuang Jiang; Shan Jiang; Han Jiang (Climatic Change, 2024)

Fine-tuning bromide AIE probes for Hg2+ detection in mitochondria with wash-free staining - Tian Tan; Chuang Zhang; Ying Han; Ruijun Chu; Wenyu Xi; Xulang Chen; Jingyu Sun; Hong Huang; Yanjun Hu; Xiaohuan Huang (Journal of Hazardous Materials, 2024)

New insights on the breakage mechanism of magnetite quartzite via high voltage pulse discharge: liberation, property difference, micro morphology, and numerical simulation - Yonghong Qin; Yuexin Han; Peng Gao; Yanjun Li; Yanxia Guo; Fangqin Cheng (Minerals Engineering, 2023)

Alternative scenarios for urban tree surveys: Investigating the species, structures, and diversities of street trees using street view imagery - Yanjun Hu; Han Wang; Hai Yan; Qian Han; Xinge Nan; Kechun Zhao; Zhiyi Bao (Science of The Total Environment, 2023)

A pilot study on recovery of iron from sulfur-bearing hematite ore using hydrogen-based mineral phase transformation followed by magnetic separation - Jianwen Yu; Hao Sun; Peiyu Li; Wenjie Han; Yanjun Li; Yuexin Han (Journal of Environmental Chemical Engineering, 2023)

Surface-bound sulfate radical-dominated degradation of sulfamethoxazole in the CuFeAl-LDH/peroxymonosulfate system: The abundant hydroxyl groups enhancing efficiency mechanism - Qing Xin; Siqi Liu; Shixu Lu; Zhenyu Chen; Pengzhan Han; Shuaishuai Xin; Qianwen Wang; Guocheng Liu; Chengzhi Zhou; Yanjun Xin; Qinghua Yan (Chemical Engineering Journal, 2023)

Novel metallic Fe recovery from copper smelting slag by the deep reduction method with renewable biochar reducing agent: Phase transformation process and Fe particle growth optimization - Bing Zhao; Xiangyan Kong; Yongsheng Sun; Yuexin Han; Yanjun Li (Process Safety and Environmental Protection, 2023)

Solubility and structural parameters of asphaltene subfractions separated from bitumen via an improved method - Hai Yuan; Azuo Nili; Jiale Chen; Haibo Ding; Han Liu; Yanjun Qiu (Fuel, 2023)

Cyanide detoxification and iron mineral recycle of cyanide tailings by the sustainable utilization technology of oxidation-reduction roasting: Process optimization and mechanism study - Bing Zhao; Lingbo Zhao; Peng Gao; Yuexin Han; Yanjun Li; Zaizheng Dong; Yan Song (Journal of Environmental Chemical Engineering, 2023)

An approach for dynamic stress-free perception of goose body mass - Yanjun Zhang; Jiawen Han; Hong Miao; Shanwen Zhang; Daoqing Gong (Biosystems Engineering, 2023)

Thermal gelation and digestion properties of hen egg white: Study on the effect of neutral and alkaline salts addition - Junhua Li; Weijian Zhang; Tingting Tang; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang; Qi Han (Food Chemistry, 2023)

Foaming properties of dried egg white at different outlet temperatures - Junhua Li; Jinjing Sun; Luping Gu; Yujie Su; Yanjun Yang; Cuihua Chang; Qi Han (Journal of Food Engineering, 2023)

Vanadium extraction from V-bearing shale using oxidation roasting and acid leaching - Xinran Zhu; Zhenya Zhou; Jianping Jin; Yanjun Li; Yuexin Han (Minerals Engineering, 2023)

Key metabolites and mechanistic insights in forchlorfenuron controlling kiwifruit development - Yingying Bi; Chengkui Qiao; Lijun Han; Hanzhong Xie; Yanjun Xu; Di Wu; Ming Zhuang; Xinru Lv; Mengyuan Cao (Food Research International, 2023)

Inversion of tight oil origin by geochemical characteristics: a case study of central Northern Shaanxi Slope, Ordos Basin - Xindi Shao; Shijia Chen; Junjie Lei; Yanjun Bai; Kai Zhou; Yang Liu; Jiang Zhu; Meimei Han (Arabian Journal of Geosciences, 2021)

Method validation, storage stability and field trial for residues of florasulam and pyroxsulam in cereal by liquid chromatography with tandem mass spectrometry - Yingying Bi; Lijun Han; Shuangyu Song; Wei Yao; Fayi Qin; Yanjun Xu; Qiong Wu (Food Additives & Contaminants: Part A, 2020)

microRNA-499a promotes the progression and chemoresistance of cervical cancer cells by targeting SOX6 - Yibing Chen; Yucen Song; Yanjun Mi; Huan Jin; Jun Cao; Haolong Li; Liping Han; Ting Huang; Xiaofei Zhang; Shumin Ren; Qian Ma; Zhengzhi Zou (Apoptosis, 2020)

Flotation and adsorption of quartz with the new collector butane-3-heptyloxy-1,2-diamine - Zhouyueyang Cheng; Yimin Zhu; Yanjun Li; Yuexin Han (Mineralogy and Petrology, 2019)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Applying support vector regression analysis on grip force level-related corticomuscular coherence - Yao Rong; Xixuan Han; Dongmei Hao; Liu Cao; Qing Wang; Mingai Li; Lijuan Duan; Yanjun Zeng (Journal of Computational Neuroscience, 2014)

Prediction of permafrost changes in Northeastern China under a changing climate - Zhi Wei; HuiJun Jin; JianMing Zhang; ShaoPeng Yu; XuJun Han; YanJun Ji; RuiXia He; XiaoLi Chang (Science China Earth Sciences, 2011)

Dissipation and Residues of Nicosulfuron in Corn and Soil Under Field Conditions - Qiong Wu; Xiaoxu Chen; Yanjun Xu; Lijun Han (Bulletin of Environmental Contamination and Toxicology, 2010)

Dissipation and Residues of Carfentrazone-ethyl in Wheat and Soil - Lijun Han; Yanjun Xu; Maofeng Dong; Chuanfan Qian (Bulletin of Environmental Contamination and Toxicology, 2007)

Dissipation and Residues of Spinosad in Eggplant and Soil - Ercheng Zhao; Yanjun Xu; Maofeng Dong; Shuren Jiang; Zhiqiang Zhou; Lijun Han (Bulletin of Environmental Contamination and Toxicology, 2007)